2005
DOI: 10.30843/nzpp.2005.58.4281
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tall fescue (<i>Festuca arundinacea</i>) endophyte (<i>Neotyphodium</i> spp) on nontarget soil nematodes

Abstract: Nontarget effects of Neotyphodium endophyte infection in fieldsown tall fescue were studied as a model for investigating nontarget effects of geneticallymodified plants Two strains of Neotyphodium endophyte (AR501 and AR542) in tall fescue at a site near Palmerston North (Aorangi) and one strain (AR501) at a site near Lincoln were sampled in March and April 2002 respectively The only consistent effect of either endophyte strain on nematode abundance was an increase of large omnivorous nematodes beneath AR501 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Live and uninjured grass grub were retained and later weighed. After removing subsamples for quantifi cation of micro-organisms (Sayer et al 2004) and nematodes (Bell 2005), roots and soil from each plot were subjected twice to a wet sieving process to extract small invertebrates. Material that was captured on both the 210 µm and 710 µm aperture sieves during each wet sieving was washed into separate specimen containers and refrigerated until counting.…”
Section: Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Live and uninjured grass grub were retained and later weighed. After removing subsamples for quantifi cation of micro-organisms (Sayer et al 2004) and nematodes (Bell 2005), roots and soil from each plot were subjected twice to a wet sieving process to extract small invertebrates. Material that was captured on both the 210 µm and 710 µm aperture sieves during each wet sieving was washed into separate specimen containers and refrigerated until counting.…”
Section: Invertebratesmentioning
confidence: 99%
“…These fungi can increase the ability of plants to forage for nutrients in soil, although grasses show little reliance on AM except under phosphorous-limiting conditions. Sayer et al (2004) and Bell (2005) have reported on, respectively, the micro-organisms and nematodes found in roots and soil samples taken from the tall fescue plots at two of the fi eld trial sites, Aorangi near Palmerston North and at Lincoln in Canterbury. In this paper information is presented on soil invertebrates, other than nematodes, that were taken from the same samples and the presence of AM in the roots.…”
Section: Introductionmentioning
confidence: 99%
“…O'Callaghan et al 2005;Squire et al 2003) there is a small but growing literature on non-target effects of novel plant-endophyte combinations, which do not involve genetic modifications (e.g. Bell 2005;Bultman et al 2009;Matthews & Clay 2001;Popay & Jensen 2005;Sayer et al 2004).…”
Section: Introductionmentioning
confidence: 99%